Impact of Spiritual Guidance on Pre-Endoscopic Anxiety: A Clinical Study - Julhana, Julhana (Adult Health Nursing Journal, 2024)
Introduction: Pre-procedural anxiety is a common psychological response among patients undergoing endoscopic examinations. This emotional state may negatively affect patient cooperation and procedural outcomes. Spiritual guidance is a non-pharmacological intervention that offers emotional and psychological comfort rooted in patients’ beliefs and values. Objectives: This study aimed to examine the effect of spiritual guidance on anxiety levels in patients prior to endoscopy. Methods: A quasi-experimental design with a time series approach was employed involving 20 adult patients. Participants received a spiritual guidance intervention consisting of structured sessions tailored to individual beliefs. Anxiety levels were measured before and after the intervention using a standardized scale. Data were analyzed using a paired t-test to determine statistical significance. Results: Prior to the intervention, 70% of patients had no family history of endoscopy and 75% had never received information about the procedure. The majority experienced moderate (45%) to severe (25%) anxiety. After spiritual guidance, anxiety levels decreased significantly, with 45% reporting no anxiety and another 45% reporting only mild anxiety. The mean anxiety score dropped from 2.90 to 1.65 (p = 0.000). Conclusions: Spiritual guidance was effective in reducing anxiety before endoscopic procedures. This finding supports the integration of spiritual care into holistic nursing practice, especially in culturally religious communities. Further research is needed to explore the long-term and broader clinical applications of this intervention.